Optimalisasi Penerapan Metoda Demonstrasi dalam Meningkatkan Hasil Belajar Siswa pada Materi Pokok Perencanaan dan Pengelolaan Perjalanan Wisata - Rodiyah, Rodiyah (Journal of Education Action Reseach, 2018)
Learning about the planning and management of tourist trips followed by students in class XI for the 2016/2017 semester 1/2017 Tourism Travel Business Skills Program results achieved by students have not reached the value according to the standard determined by the school, namely 80. Based on initial observations by the author achieved by students for the subjects of planning and management of tourist trips is still low at 69.2 with learning completeness reaching 43.33%. The purpose of this study is to improve the learning outcomes of tourism travel business with material for planning and managing tourist trips through the application of demonstration methods. The research method used is descriptive, the type of research is class action. The research subjects were 30th grade students of UPW in the First Semester of the State Vocational School of Jakarta 60 in total. The technique used is direct observation. Data collection tools are teacher and student observation sheets. This research was carried out through two cycles, the research procedure using the stages of planning, implementation, observation and reflection. Based on the research that has been done the results obtained in the first cycle the average value of 77.2, while in the second cycle of 81.96. Based on the results of the study it can be concluded that by applying the demonstration method in learning Planning and managing travel trips can improve the learning outcomes of the XI class of UPW Vocational High School 60 Jakarta well.